Cinematic rendering of paediatric musculoskeletal pathologies: initial experiences with CT. Issue 4 (April 2022) - Fagan, A.; Arthurs, O.J.; Sebire, N.J.; Shelmerdine, S.C.
Abstract : Cinematic rendering (CR) is a novel post-processing technique similar to volume rendering (VR), which allows for a more photorealistic imaging reconstruction by using a complex light modelling algorithm, incorporating information from multiple light paths and predicted photon scattering patterns. Several recent publications relating to adult imaging have argued that CR gives a better "realism" and "expressiveness" experience over VR techniques. CR has also been shown to improve visualisation of musculoskeletal and vascular anatomy compared with conventional CT viewing, and may help non-radiologists to understand complex patient anatomy. In this review, we provide an overview of how CR could be used in paediatric musculoskeletal imaging, particularly in complex diagnoses, surgical planning, and patient consent processes. We present a direct comparison of VR and CR reconstructions across a range of congenital and acquired musculoskeletal pathologies, highlighting potential advantages and areas for further research. Highlights: Cinematic rendering (CR) is a novel 3-D post-processing technique which uses a specalised light scattering algorithm. Uses of CR include improved anatomical visualisation. This can aid patient consent, medical education and surgical planning. Further work comparing the clinical and cost effectiveness of CR with other modelling tools in children's imaging is needed.